2018
DOI: 10.5089/9781484374931.001
|View full text |Cite
|
Sign up to set email alerts
|

The Fiscal Cost of Conflict: Evidence from Afghanistan 2005-2016

Abstract: I use a monthly panel of provincially-collected central government revenues and conflict fatalities to estimate government revenues lost due to conflict in Afghanistan since 2005. I identify causal effects by instrumenting for conflict using pre-sample ethno-linguistic share. Headline estimates are very large, implying total revenue losses since 2005 of $3bn, and future revenue gains from peace of about 6 percent of GDP per year. Reduced collection efficiency, rather than lower economic activity, appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Internal instability impedes on government revenue by disrupting economic activity, destroying the tax base, and lowering the efficiency of tax administration (IMF, 2019). Barrett (2018) showed that the conflict in Afghanistan led to a total revenue loss of about US$3 billion between 2005 and 2016, resulting mainly from a significant decline in revenue collection efficiency. Similarly, Rother et al (2016) emphasised that central government revenue collapsed by about 60% following the outbreak of the conflict in Yemen in 2015.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Internal instability impedes on government revenue by disrupting economic activity, destroying the tax base, and lowering the efficiency of tax administration (IMF, 2019). Barrett (2018) showed that the conflict in Afghanistan led to a total revenue loss of about US$3 billion between 2005 and 2016, resulting mainly from a significant decline in revenue collection efficiency. Similarly, Rother et al (2016) emphasised that central government revenue collapsed by about 60% following the outbreak of the conflict in Yemen in 2015.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Gupta et al (2004) and Cevik and Ricco (2015) show that armed conflict not only has adverse effects on tax revenues, but also changes the composition of government spending through the increase in defense spending. The findings in Barrett (2018) also underscore the considerable fiscal loss caused by an extended major conflict.…”
Section: Introductionmentioning
confidence: 68%
“…Cárdenas (2010), Thies (2005) and Lu and Thies (2013) empirically support this argument using cross-country evidence from Latin America and the Middle East. Likewise, Barrett (2018) and Jibao, Prichard, and Van den Boogaard (2017) find the same adverse effects of conflict using within-country data from Afghanistan and Sierra Leone, respectively. While the former uncovers a negative impact of conflict on provincially-collected central government revenues, the latter present evidence of weak fiscal institutions in the aftermath of civil war.…”
Section: Introductionmentioning
confidence: 69%